Circulation and Thermohaline Variability of the Hanna Shoal Region on the Northeastern Chukchi Sea Shelf. Issue 7 (8th July 2020) - Fang, Ying‐Chih; Weingartner, Thomas J.; Dobbins, Elizabeth L.; Winsor, Peter; Statscewich, Hank; Potter, Rachel A.; Mudge, Todd D.; Stoudt, Chase A.; Borg, Keath
Abstract: We analyzed velocity and hydrographic data from 23 moorings in the northeast Chukchi Sea from 2011 to 2014. In most years the eastern side of Hanna Shoal was strongly stratified year‐round, while weakly stratified regions prevailed on the shelf south and west of the Shoal. Stratification differences cause differential vertical mixing rates, which in conjunction with advection of different bottom water properties resulted in seasonally varying along‐isobath density gradients. In agreement with numerical models, we find that bottom waters flow anticyclonically around the Shoal. Whereas most of the shelf responded barotropically to wind‐forcing, there was a strong baroclinic component to the flow field northeast of Hanna Shoal, resulting in no net vertically integrated transport on average. In contrast there is a net eastward transport from west of the Shoal, which implies convergence north of the Shoal. Convergence and along‐isobath density gradients may foster cross‐shelf exchange north of Hanna Shoal. Modal analyses indicate that the shelf south of the Shoal and Barrow Canyon responded coherently to local and remote winds, whereas the wind‐current response around Hanna Shoal was less coherent. Barotropic topographic waves, of ~3‐day period, were generated episodically northeast of the Shoal and propagate clockwise around Hanna Shoal, but are blocked from entering Barrow Canyon and are possibly scattered by the horizontally sheared flow and converging isobaths on the western side of the Shoal. Analysis of water properties on the western side of Hanna Shoal suggests that these include contributions from the western and southern portions of the Chukchi Sea. Plain Language Summary: We use multiyear mooring measurements of velocity and hydrography to elucidate the circulation in the Hanna Shoal region on the northern Chukchi shelf. Hanna Shoal is a biological hot spot but has only recently received attention due to historically heavy summer sea ice cover. We find that on the eastern side of Hanna Shoal the water column is perpetually stratified and currents are strongly sheared in contrast to other locations in the northeastern Chukchi Sea. Our results imply that the shelf north of Hanna Shoal may be a site for water mass exchange between the shelf and shelfbreak. This topic deserves further study in order to determine the pathways by which Pacific and Arctic Ocean waters interact. Key Points: Stratification on the eastern side of Hanna Shoal is maintained year‐round, unlike other locations on the northeastern Chukchi shelf Baroclinic flows driven by winter‐evolved along‐isobath density gradients are pronounced in winter on the eastern side of Hanna Shoal A coherent signal with a ~3‐day period circulating Hanna Shoal is described, with features consistent to a barotropic topographic wave